Optimality and overuse of labour in Estonian manufacturing enterprises - Jaan Masso; Almas Heshmati (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
For transition economies labour market flexibility is necessary for successful restructuring and reallocation of labour force and for coping with the requirements of the European Monetary Union. In this paper we apply a novel approach to the issue of labour market flexibility in transition countries by studying the optimality and efficiency of labour usage among Estonian manufacturing enterprises. A dynamic model is employed where both the long run optimal level of employment and the speed at which actual employment is adjusted to the optimal are modelled as functions of several variables. Firm level panel data from 1995 to 1999 were used. The results showed that in the long run employment responds greatest to wages, followed by valueadded and capital stock. Speed of adjustment and labour use optimality and efficiency show much greater variations over firms than over time. In the course of time there occurs both labour saving technical change and an increase in the efficiency of labour usage. On average there is shortage of labour compared to firm's own optimal level, while over use of labour compared to best-practice technology. Capital seems to be a binding constraint on the development of employment in the Estonian labour market. – labour ; efficiency ; employment ; flexibility ; Estonia
Keywords: C23; J23; P23; 330; Arbeitsmarkt; Arbeitsnachfrage; Arbeitsmarktflexibilisierung; Estland